Energy-delay efficient data memory subsystems suitable for embedded media "processing". - Ramachandran, A. (IEEE Signal processing magazine)
This article presents a novel special-purpose data memory subsystem, called Xtream-Fit, suitable for embedded media processing, and demonstrates how it achieves high energy-delay efficiency across a wide range of media devices, including systems concurrently executing multiple applications under synchronization constraints. Experimental results show that Xtream-Fit delivers a substantial improvement in energy-delay product, as compared to general-purpose memory subsystems enhanced with state of-the-art cache decay and SDRAM dynamic power mode control policies. Xtreams-Fit's performance is predicted on a novel, task-based execution model that enhances opportunities for efficient stream granularity prefetching and aggressive software-based energy conservation techniques.